2019
DOI: 10.1016/j.ejca.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre retrospective cohort study of ovarian germ cell tumours: Evidence for chemotherapy de-escalation and alignment of paediatric and adult practice

Abstract: Background Adult guidelines recommend BEP (bleomycin, etoposide, cisplatin) for all ovarian germ cell tumours, causing debilitating toxicities in young patients who will survive long term. Paediatricians successfully reduce toxicities by using lower bleomycin doses and substituting carboplatin for cisplatin, while testicular and paediatric immature teratomas (ITs) are safely managed with surgery alone. Aim The aim was to determine whether reduced-toxicity treatment coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 27 publications
6
57
2
Order By: Relevance
“…Some of the authors of this review have recently published a retrospective series of ovarian germ cell tumours, concentrating on a number of different factors . First, on review, even small areas of other elements meant assignation to a mixed germ cell tumour rather than a pure IT.…”
Section: Immature Teratomasmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the authors of this review have recently published a retrospective series of ovarian germ cell tumours, concentrating on a number of different factors . First, on review, even small areas of other elements meant assignation to a mixed germ cell tumour rather than a pure IT.…”
Section: Immature Teratomasmentioning
confidence: 99%
“…Event‐free survival according to ( A ) FIGO stage, ( B ) histological OvGCT subtype, ( C ) patient age at diagnosis and ( D ) grade of immature teratoma. OvGCT, ovarian germ cell tumour; Dys, dysgerminoma; IT, teratoma; YST, yolk sac tumour; MGCT, mixed germ cell tumour; PNET, primitive neuroectodermal tumour; HR, hazard ratio; CI, confidence interval (from Newton et al …”
Section: Immature Teratomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Confirmation of the wider applicability of this approach, i.e. avoiding adjuvant chemotherapy after surgery for IT, came from a recent report describing ovarian IT in adult patients [27]. Newton et al studied 138 patients across four large UK cancer centres over 12 years; EFS was 72% and OS 93% [27].…”
Section: The Role Of Adjuvant Chemotherapy For Ovarian Immature Teratomamentioning
confidence: 99%
“…avoiding adjuvant chemotherapy after surgery for IT, came from a recent report describing ovarian IT in adult patients [27]. Newton et al studied 138 patients across four large UK cancer centres over 12 years; EFS was 72% and OS 93% [27]. They showed that adjuvant chemotherapy did not reduce future relapse or progression in IT patients and they observed no radiologic responses to chemotherapy in IT.…”
Section: The Role Of Adjuvant Chemotherapy For Ovarian Immature Teratomamentioning
confidence: 99%